2019
DOI: 10.1097/rct.0000000000000834
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Moyamoya Disease and Moyamoya Syndrome: Current Status

Abstract: Moyamoya disease (MMD) and Moyamoya syndrome (MMS) are referring to a progressive steno-occlusive vasculopathy at terminal portions of the bilateral internal carotid arteries and their proximal branches with prominent collateral artery formation. They can be found throughout the world and cause irreversible damage to the cerebral hemodynamics due to the progressive nature. Prompt diagnosis and accurate assessment could significantly improve the prognosis of MMD and MMS. Some imaging modalities could be used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 58 publications
1
52
0
1
Order By: Relevance
“…Diffusion and perfusion magnetic resonance, single photon emission computed tomography, and/or advanced MRA techniques can reliably demonstrate vessels occlusion and/or parenchymal hypoperfusion or infarcts, both on symptomatic and asymptomatic patients. [ 36 37 38 ] Moreover, these modern techniques can point out reperfusion candidates or evaluate surgical results.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion and perfusion magnetic resonance, single photon emission computed tomography, and/or advanced MRA techniques can reliably demonstrate vessels occlusion and/or parenchymal hypoperfusion or infarcts, both on symptomatic and asymptomatic patients. [ 36 37 38 ] Moreover, these modern techniques can point out reperfusion candidates or evaluate surgical results.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Among these, CVR may be the most valuable indicator to reflect the cerebral hemodynamic changes of MMD patients. 46 …”
Section: Related Factorsmentioning
confidence: 99%
“…48 Among these, CVR may be the most valuable indicator to reflect the cerebral hemodynamic changes of MMD patients. 46 In order to compensate for the decreased cerebral perfusion, three major collateral pathways develop 49,50 : (1) basal moyamoya perforator vessels arising from the anterior two-thirds of the circle of Willis. Indeed, in 2009, Kawashima et al found that unilateral hemispheric ivy proliferation correlated highly with the existence of an ipsilateral decreased CVR associated with the development of leptomeningeal collaterals in patients with MMD.…”
Section: Angiographymentioning
confidence: 99%
“…Cerebral hemodynamics may be assessed with a variety of perfusion imaging techniques, including several nuclear medicine methods, contrast-bolus or xenon CT, and several MRI methods that have been extensively reviewed previously. 2,37,40,44,73 These vary in both qualitative or quantita-tive capability and type of information provided, but in general provide measures of CBF, cerebral blood volume (CBV), mean transit time (MTT), time to peak (TTP), and/or relative oxygen extraction. 2,38,40,44,73 An understanding of the underlying pathophysiology is essential for the application and interpretation of imaging examinations that assess cerebral perfusion and CVR.…”
Section: Cerebral Perfusion and Cerebrovascular Reactivitymentioning
confidence: 99%